INTEGRASI ILMU NAQLIYAH DAN AQLIYAH: TAWARAN EPISTEMOLOGIS BAGI ARAH BARU PENGEMBANGAN PENDIDIKAN ISLAM - Imam Makhrus; Komarudin Sassi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The epistemological crisis in Islamic education arises from the persistent dichotomy between naqliyah (revelational) and aqliyah (rational) sciences. Modern Islamic education often falls into formalism and loses its transformative spiritual power. This paper proposes a new epistemological framework integrating both naqliyah and aqliyah sciences as the foundation for a holistic development of Islamic education. Using a qualitative library research approach with hermeneutic analysis, this study explores the epistemological relation between revelation and reason in classical and contemporary Islamic thought. The findings reveal that integrating these two knowledge domains produces an integrative-holistic epistemology that emphasizes not only knowledge transmission but also spiritual and moral formation. This epistemological offer provides a new direction for curriculum development, learning design, and Islamic educational methodology rooted in tawhid and rationality values.